The domain of reasons - Skorupski, John, 1946- (Oxford : Oxford University Press, 2010)
This text is about normativity and reasons. But by the end the subject becomes the relation between self, thought and world. Skorupski argues that the key concepts of epistemology and moral theory are normative concepts, and that what makes them normative is that they depend on reasons.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Reason; Normativity (Ethics); Knowledge, Theory of; Thought and thinking